Effect of the increase in table-tennis ball size - Wei, X. (2002)
Since October 2000, when the International Table Tennis Federation (ITTF) decided to increase the size of table-tennis balls used in the game, the newly-sized ball has been adopted in all international table-tennis competitions. The new ball is different from the old in both diameter and weight. Through this change, the speed and spin of the ball will be reduced, and the number of strokes in rally increased, thus making the table-tennis match more interesting. If you are wondering what the effects of the increase in table-tennis ball size are, here's a low-down on the technicalities: What is the change of the new ball in size and weight? The increase in weight is about 0.2g (NITTAKU from 2.49g to 2.67g, DOUBLE HAPPINESS from 2.47 to 2.75) and increase in diameter is 2mm (from 38mm to 40mm). With the larger ball, the player may feel a greater impact on striking. However, he or she will probably get used to this after a period of practice. What is change of in the speed and spin? The speed and power at which the ball is struck will determine the speed of the ball. A stronger impact will result in a faster ball speed and gives a shorter time for the opponent to react. In addition to the collision of the ball with the table and racket surfaces, the spin of the ball also contributes to the overall path taken by the ball. The ability to control spin will increase the chance of a successful match outcome by making it difficult for the opponent to return the ball. Thus, data on speed and spin is helpful for players seeking to improve technique and training efficiency. Research data from the Biomechanics Laboratory of the Singapore Sports Council shows that both the average speed and spin of the bigger 40mm ball are less than that of the 38mm ball. The percentage of the decrease varies, depending on the player and technique. For the players tested, the reduction of speed is less than 7.9% in the forehand smash, 2.8% in the forehand drive loop and 6.8% in the forehand high loop. The reduction of spin is less than 15.4% in the forehand smash, 12.0% in the forehand drive loop, 7.7% in the forehand high loop and 10.8% in the service. Can the techniques of table tennis players be evaluated? Yes, the test of the speed and spin is an effective way to evaluate the table tennis player's technique, the rubber used and playing styles. It's applicable not only for elite, but also junior players. The Biomechanics Unit of the Sports Medicine & Research Centre can provide this test.